2021
DOI: 10.1111/evj.13484
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric dimethylarginine and renal function analysis in horses with dehydration

Abstract: Background: Acute dehydration caused by a variety of diseases in horses can lead to acute kidney injury. However, current renal biomarkers usually indicate renal damage late in the course of the disease. A novel biomarker would be helpful to diagnose renal disease earlier.Objectives: 1) To estimate the correlation of serum symmetric dimethylarginine (SDMA) concentrations with the degree of dehydration, traditional renal biomarkers and renal function analysis, and 2) to determine the value of SDMA as a prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Similar to SDMA in other species, factors that impact GFR also influence SDMA [ 12 ]. This has been confirmed by elevated SDMA in dehydrated horses [ 19 ] and in exercising endurance horses [ 13 ].…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…Similar to SDMA in other species, factors that impact GFR also influence SDMA [ 12 ]. This has been confirmed by elevated SDMA in dehydrated horses [ 19 ] and in exercising endurance horses [ 13 ].…”
Section: Resultsmentioning
confidence: 76%
“…These showed different serum concentrations of SDMA between (1) healthy horses versus horses with AKI [ 18 , 19 ], (2) horses with different levels of dehydration [ 19 ], and (3) endurance horses before versus after the race, with post-race SDMA concentrations being higher with longer racing distance [ 13 ]. There was no difference in serum SDMA concentrations between healthy horses versus horses with cardiac disease [ 14 ], or between survivors and non-survivors with different degrees of dehydration (lower SDMA concentrations were found in survivors than in non-survivors, however this was not statistically different) [ 19 ]. SDMA concentrations have only been reported on very few equine AKI cases (37 cases divided over 4 studies) [ 15 , 16 , 18 , 19 ], and so far on no confirmed equine CKD cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood urea nitrogen (BUN) has no direct linear correlation with GFR and is also affected by factors such as diet and liver function [9]. In a previous study investigating symmetric dimethylarginine (SDMA), which is also a novel renal biomarker, we described a correlation between serum SDMA concentration and creatinine: a signi cant correlation was found and SDMA at admission differed among dehydration levels, but the distribution of SDMA in the 3 groups overlapped easily with each other [10]. Further research is still needed to identify the role of SDMA in equine renal disease.Neutrophil gelatinase-associated lipocalin (NGAL) is a protein originally detected in activated neutrophils.…”
mentioning
confidence: 99%